A laboratory data-based evaluation of the efficacy and safety of generic pravastatin sodium for long-term use. Issue 1 (December 2016) - Suzuki, Masanori; Kanamori, Motoyasu; Hashimoto, Tomoaki; Hashimoto, Yuji; Funakoshi, Ryohkan; Sasaki, Tadanori
Abstract Background Increasing the use of generic drugs may reduce the growing healthcare spending. Nevertheless, in Japan, the generic drug market share remains low compared to that of European countries and the United States, mainly because of the general distrust of generic drugs. To address this problem, we retrospectively evaluated the efficacy and safety of the long-term use of generic pravastatin sodium in a study from January 2008 to December 2011. Methods Patients receiving generic pravastatin sodium for ≥15 months were defined as long-term users and were included in the study, totaling 595 out of 1337 patients. Efficacy assessment was based on the total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) plasma levels. Safety assessment was based on the aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatine phosphokinase (CPK), gamma-glutamyl transferase (γ-GTP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), total-bilirubin (T-Bil), blood urea nitrogen (BUN), serum creatinine (Scr), and hemoglobin A1c (HbA1c) plasma levels. The patients' reasons for discontinuing generic pravastatin sodium were obtained from the electronic medical records. Results & discussion No significant difference in the laboratory data was observed between short-term and long-term users, except for significantly lower ALT levels in the long-term users than in the short-term users. No liver dysfunction was observed. Although 37 patients discontinued the study possibly owing to drug-related adverse events, we considered these events unrelated to generic pravastatin sodium. Conclusions This study shows that the long-term use of generic pravastatin sodium is effective and safe, and may help dispel the concerns about generic drugs.